TECHNOLOGIES FOR IMPROVING THE QUALITY OF PHYSICAL TRAINING OF YOUNG JUDOKA GIRLS DURING TRAINING - Matmuratova Iroda Bakhtiyarovna (Academia Science Repository, 2023)
Physical training is a critical component of a young judoka girl's development. To improve their performance, they need to have a proper training regime that combines various exercises and techniques. Technology has advanced significantly over the years, and it can be used to improve the quality of physical training. In this article, we will explore various technologies that can be used to improve the quality of physical training for young judoka girls.